The Influencing Risk Factors of Measles in Bantul Regency - Susilowati, Anik; Wijayanti, Yuni; Made Sudana, I (Universitas Negeri Semarang, 2019)
Measles is the causeÃ‚Â infant and child deaths that occur in developing countries,Ã‚Â WHO states that measles cases are reported to have increased by 300% in the first month of 2019 compared to 2018. Africa is the most significant increase of 70% in the world. Ukraine, Madagascar and India are the worst affected countries, with tens of thousands of cases registered for every million of its population. Since September, at least 800 people have died from measles in Madagascar . The purpose of this study was to analyze the risk factors that influence the incidence of measles in infants. This research was a quantitative research, with a Case Control Study approach. The research sample consisted of 122 respondents with Purposive Sampling. Data analysis used univariate, bivariate and multivariate analysis using multiple linear regression. The results showed that knowledge (p = 0.003), nutritional status (p = 0,000), parenting (p = 0.029) and behavior influenced the incidence of measles in infants (p = 0.034). Furthermore, multivariate analysis showed that the risk factors for measles in infants were knowledge, nutritional status, parenting and behavior. The community is expected to improve parenting and healthy behavior, especially related to factors that can prevent measles in an effort to increase prevention of comprehensive diseasesÃ‚Â